2005
DOI: 10.1111/j.1540-6210.2005.00442.x
|View full text |Cite
|
Sign up to set email alerts
|

Race, Sex, and Clarence Thomas: Representation Change in the EEOC

Abstract: The theory of representative bureaucracy concerns whether bureaucracy mirrors the origins and values of the population and, if so, whether such representation makes any difference. This article extends Hindera's examination of active bureaucratic representation within the Equal Employment Opportunity Commission (EEOC) to determine the effect of introducing new goals (disability discrimination) and priorities (sexual harassment) on the EEOC's representational patterns. Using data from the late 1980s and late 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 31 publications
3
40
0
Order By: Relevance
“…Female representation was analyzed at various levels of the federal bureaucracy—including overall female representation in an agency, female representation in senior executive positions, and female representation among contracting officers—and in no case was evidence found of passive gender representation translating into overall substantive benefits for women. This finding is consistent with some previous research (Meier, Pennington, and Eller ). There are several possible explanations for this overall trend in the agencies that we observed.…”
Section: Resultssupporting
confidence: 94%
“…Female representation was analyzed at various levels of the federal bureaucracy—including overall female representation in an agency, female representation in senior executive positions, and female representation among contracting officers—and in no case was evidence found of passive gender representation translating into overall substantive benefits for women. This finding is consistent with some previous research (Meier, Pennington, and Eller ). There are several possible explanations for this overall trend in the agencies that we observed.…”
Section: Resultssupporting
confidence: 94%
“…Most of the PAR scholarship that includes an equity focus on race/ethnicity and/or gender is concentrated in the area of representative bureaucracy. This literature examines an assorted combination of these groups and their representation in the public sector relative to employment, wages, or position (see, e.g., Brereton ; Cayer and Sigelman ; Cornwell and Kellough ; Dometrius and Sigelman ; Hopkins ; Howard ; Hellriegel and Short ; Kellough ; Lewis , ; Lewis and Frank ; Meier and Nigro ; Meier, Pennington, and Eller ; Naff and Crum ; Rehfuss ; Riccucci and Saidel ; Saltzstein, Ting, and Saltzstein ; Soni ; Wise ).…”
Section: Milestones On the Social Equity Timelinementioning
confidence: 99%
“…Th e fi rst PAR article focused on Latinos, "Th e Chicano Experience with Nativism in Public Administration" appeared in the November/December 1974 issue. As Diaz de Krofcheck and Jackson explain, "Th e Spanish-surname minority group is the second largest minority in the U.S., but has been perceived by some as a nonminority, or as an 'invisible minority Meier and Nigro 1976;Meier, Pennington, and Eller 2005;Naff and Crum 2000;Rehfuss 1986;Riccucci and Saidel 1997;Saltzstein, Ting, and Saltzstein 2001;Soni 2000;Wise 1990).…”
Section: Rose and Chia's Analysis Of The Equalmentioning
confidence: 99%
“…Research related to representative bureaucracy has remained central to the study of race and gender. Meier, Pennington, and Eller (2005) demonstrated that despite the fact that more women were employed at the Equal Employment Opportunity Committee, the increased representation did not result in an increase of complaints filed by women. Important studies have focused on the representation of women in state agencies, including agency leadership (Bowling, Kelleher, Jones, & Wright, 2006;Saidel & Loscocco, 2005), the representation of women in leadership in non-profit organizations (Pynes, 2000), and explorations of differences in salary between male and female school superintendents (Meier & Wilkins, 2002).…”
Section: A Time For Reflectionmentioning
confidence: 99%